How to Understand the International Students with Whom You Work - Gaulee, Uttam (Journal of International Students, 2018)
Are international students needy? Are they intractable? Do they plagiarize? Are they inefficient in writing? Do they negotiate grades? Are these ontological questions? Is everything they do a manifestation of their being international students? Or is there a way to understand, first, the students as human beings? Perhaps what they do is not because they are international students. Let’s face it: Internationals are strong. They are not here to receive our tender love and care. What they do need from us, fairly, is one thing, and that is understanding. It is important for college and university officials who work with international students to try to understand their students. Recognizing the international students as human beings like local students is the first step, one that goes a long way. Ask this question to yourself: what would a domestic student do in a similar situation? If the domestic student would do the same, then do not say that the international student did such and such because he or she is an international student. It’s because he is a human being.